Assessment of Suspended Particulate Matter (SPM) and Toxicity Potential (TP) of Emissions from Different Power Generating Sets in Ado-Ekiti, Nigeria - Kolawole, Omobusuyimi Matthew; Omole, Olusola Olayemi; Adesina, Olusola Adedayo (ABUAD Journal of Engineering Research and Development (AJERD), 2023)
This research investigated the levels of Suspended Particulate Matter (SPM) resulting from the emissions of various power generators in Nigeria. Additionally, the study conducted risk assessments concerning the inhalation of this pollutant from different power generators, and proposed suitable measures to control the emission of SPM linked to the use of power generators. To capture the exhaust from each generator set, a sampling technique was employed. This involved using a sample probe, a filter, and a filter holder to trap the gas emissions in a sequential manner. The concentration of SPM in the air was calculated based on several factors, including the weight difference of the filter paper before and after sampling, the sampling duration, and the flow rate. The concentration of suspended particulate matter for the 16 different generating sets varied from 1413.4 µg/m3 to 5300 µg/m3, with an average concentration of 2912.98 µg/m3. These values surpassed both the World Health Organization (WHO) standard of 50 µg/m3 and the Nigeria Ambient Air Quality Standard of 250 µg/m3. The study’s findings indicate that power generating sets emit Suspended Particulate Matter (SPM) through their gas exhaust. Moreover, the results demonstrate that the generator samples lacking a galvanized mesh at the gas stream exhaust exhibit significantly higher toxicity potential compared to those with the galvanized mesh. This research established that SPM concentrations were found from the exhaust of different power generating sets.